2016
DOI: 10.11621/pir.2016.0203
|View full text |Cite
|
Sign up to set email alerts
|

Russian students’ awareness of and attitudes toward donating to biobanks

Abstract: Today in Russia and all over the world significant efforts are invested in building biobanks-specialized facilities for storing biological materials for research and medical purposes. The successful functioning of biobanks depends directly on people's willingness to donate their biological materials. No previous studies of people's attitudes toward donations to biobanks have been undertaken in Russia. The goal of this study was to measure attitudes toward biobank donation among young Russians and to evaluate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
1
10
0
4
Order By: Relevance
“…The term “biobank” appears to be new to almost half of student respondents from all disciplines whereas only 52.9% of the students stated that they have previous knowledge of the term. This figure is better than the 27% of Saudi healthcare students [ 11 ], the 40% of Egyptian medical students [ 12 ], and the 20% of Russian students [ 13 ] who knew what the term meant. However, it is less than the 83.7% of students of the Italian Padua University who were able to select the right definition from a multiple-choice question [ 14 ].…”
Section: Discussionmentioning
confidence: 91%
“…The term “biobank” appears to be new to almost half of student respondents from all disciplines whereas only 52.9% of the students stated that they have previous knowledge of the term. This figure is better than the 27% of Saudi healthcare students [ 11 ], the 40% of Egyptian medical students [ 12 ], and the 20% of Russian students [ 13 ] who knew what the term meant. However, it is less than the 83.7% of students of the Italian Padua University who were able to select the right definition from a multiple-choice question [ 14 ].…”
Section: Discussionmentioning
confidence: 91%
“…willingness to participate in biobanking among university students in Russia [12]. On the other hand, the survey conducted among students in Italy showed that gender has a signi cant association on participation [13].…”
Section: Discussionmentioning
confidence: 96%
“…The term "biobank" appears to be new to almost half of student respondents from all disciplines where only 52.9% of the students stated that they have a previous knowledge of the term. This gure is better that the 27% Saudi healthcare students [10], the 40% of Egyptian medical students [11], and the 20% of Russian students [12] who knew what the term means. However, it is less than students of the Italian Padua University who a large percentage of them were able to select the right de nition from a multiplechoice question [13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is still minimal knowledge about Russian biobank donors' motivation and experience [18; 19; 20]. In 2014, a study among Russian University students showed a little awareness regarding biobanks (21%), together with a relatively high level of willingness of the Russian youth to donate to that (74%); a minimal impact of value orientations, and the lack of in uence of socio-demographic variables on the willingness to donate [20]. The predictive factors of willingness to biobank donation, among Russian university students and researchers, were awareness of the biobank, approval of members of their close social environment, donation fees, and the type of biological material requested [21].…”
Section: Introductionmentioning
confidence: 99%